Filling biogeographic gaps about the shrimp Farfantepenaeus isabelae Tavares & Gusmão, 2016 (Decapoda: Penaeidae) in South America - França, Nielson F. C.; Alencar, Carlos E. R. D.; Mantelatto, Fernando L.; Freire, Fúlvio A. M. (Zootaxa, 2020)
Farfantepenaeus isabelae is a recently described pink shrimp species with occurrence restricted to the South Atlantic. The real geographic distribution of this species is still uncertain, probably due to difficulties on identification in relation to congeners. The present study aims to increase the knowledge about its occurrence by using an integrative approach with morphology, molecular and niche modeling analysis. Our results extend both western and eastern limits of occurrence of F. isabelae, elucidating gaps along the northern region of Brazil. The knowledge about its distribution will contribute to updating the politics of management and fishing in order to preserve its natural stocks.